La interferencia de la violencia intrafamilia en el aprendizaje del inglés. Un estudio independiente. - Oye, Peter Rotimi (2016)
This research had its origin in the difficulties of learning the English language of a student with economic problems and violence in his family and who could not pass the second level of English language at the University. He had 'phobia' for learning English because of previous bad experiences and an online method of teaching and learning English that is not suitable for beginners. The method of 'one to one' has been initially applied with the achievement of a very high motivation toward learning the English language. However, the student failed to pass the second level of English. Due to this fact, a psycho-pedagogical and language evaluation was requested to find out the causes for which the method applied could not bring the expected results. It was discovered that the student suffered from a 'phonological dyslexia' and therefore the used method may be subject to further research. The theoretical foundation of this field work consisted of a case study. Structured interview was used as a tool necessary in order to identify important facts about his experience in childhood and adolescence and the effects of violence interactions in the crucial stages of his live. We concluded this investigative work that violence badly affects the learning processes. In this case, it was focused on the acquisition and development of the student`s language as well as the ability to understand abstraction with concrete learning based solely on objective experiences. A study based on constructivist theories was applied to this case. It could be concluded that experiences in society have been the reason for him to develop certain types of withdraw from others company. Interpersonal communication and the uses of acceptable language were affected negatively. Emotions have a close link in the acquisition of learning in students. The methodological strategy of "One to One" did not work because the basis of the problems are in the experiences and negative emotions that even the student has failed to remove, which in turn affected him and his environment.